Family-Based Business Groups: Degeneration of Quasi-Internal Organizations and Internal Markets in Korea - Sang-woo Nam (Asian Development Bank Institute (ADBI), 2001)
At the early stages of development, a close government-business partnership (here a QIO) and internal markets within a business group can often be advantageous. But as economies mature and are exposed to more complex and uncontrollable factors, including globalization, governments and businesses need to grow out of these limiting QIOs and internal markets. Otherwise, as the author shows, they run the risk of being stuck with a worn-out, inefficient, and potentially corrupting system.
hdl:11540/4134
Keywords: 330